Problematic concept in the linguistic term" "al’ielal model". - محمد أبو الهيجاء يس (Journal of College of Education, 2019)
This research deals with the problem of " al’ielal ". It is based on research on the problematic between the term " al’ielal " and its concepts, which were mixed with other terms and concepts. Through the treatment of linguists to the phenomenon of " al’ielal ", in the first place, and other verbal and vocal phenomena in the second. And "al’ielal" the most prominent - if not the most prominent - vocal phenomena, which linguists have addressed since their first efforts. While the term is confined to its first purpose, His ideas were extended, in circles beyond the vowels, And entered other areas such "’ibdal",and "alqlb"and "alhadhf" and, in the broad sense. This confusion was reflected in many other issues, the most prominent of which are: the definition of the concept of "aetlal Letter" , and the morphological and sound issues related to the "lhamz", and the combination of "al’ielalyn". In spite of the frequent dealing with the phenomenon of " al’ielal " old and modern, but we find no stop on this aspect of the term. The research deals with the multiple fluctuations of the concepts of this term, which were manifested in the treatment of linguists of the phenomenon of " al’ielal ", in the first place. Leaving the halo of the term, and its implications that emerged from them as they are. It takes care of investigating this term and tracking its concepts among the most prominent linguists, since its emergence to the efforts of contemporary. As it tracks its courses in terms of formulation, and address the linguists to the main issues, and then investigate the emergence of this problem in his definition. In the most prominent private and public expressions, encyclopedias, old and modern. It seeks to form a clear picture of the term "al’ielal", and its problematic mechanisms of definition and application, necessarily ending with the monitoring and characterization of one of the most important problems of the traditional linguistic term, which is the sanctity of the term and the rebellion of its concepts. It is - after - a modest brick, in the construction of hope, namely, the historical lexicon of Arabic linguistic terms.